Comparative Evaluation of Participation and Diagnostic Yield of Colonoscopy vs Fecal Immunochemical Test vs Risk-Adapted Screening in Colorectal Cancer Screening: Interim Analysis of a Multicenter Randomized Controlled Trial (TARGET-C). (August 2020) - Chen, Hongda; Lu, Ming; Liu, Chengcheng; Zou, Shuangmei; Du, Lingbin; Liao, Xianzhen; Dong, Dong; Wei, Donghua; Gao, Yi; Zhu, Chen; Zhu, Liming; Zheng, Weifang; et al.
Abstract : INTRODUCTION: In colorectal cancer screening, implementing risk-adapted screening might be more effective than traditional screening strategies. We aimed to compare the effectiveness of a risk-adapted screening strategy with colonoscopy and fecal immunochemical test (FIT) in colorectal cancer screening. METHODS: A randomized controlled trial was conducted in 6 centers in China since May 2018. Nineteen thousand five hundred forty-six eligible participants aged 50–74 years were recruited and randomly allocated into 1 of the 3 screening groups in a 1:2:2 ratio: (i) one-time colonoscopy (n = 3, 916), (ii) annual FIT (n = 7, 854), and (iii) annual risk-adapted screening (n = 7, 776). Based on the risk-stratification score, high-risk subjects were referred for colonoscopy and low-risk ones were referred for FIT. All subjects with positive FIT were referred for diagnostic colonoscopy. The detection rate of advanced neoplasm was the primary outcome. The study is registered with the China Clinical Trial Registry (www.chictr.org.cn Identifier: ChiCTR1800015506). RESULTS: For baseline screening, the participation rates of the colonoscopy, FIT, and risk-adapted screening groups were 42.5% (1, 665/3, 916), 94.0% (7, 386/7, 854), and 85.2% (6, 628/7, 776), respectively. For the intention-to-screen analysis, the detection rates of advanced neoplasm were 2.40% (94/3, 916), 1.13% (89/7, 854), and 1.66% (129/7, 776), with odds ratios (95% confidence intervals) of 2.16 (1.61–2.90; P < 0.001) for colonoscopy vs FIT, 1.45 (1.10–1.90; P < 0.001) for colonoscopy vs risk-adapted screening, and 1.49 (1.13–1.97; P < 0.001) for risk-adapted screening vs FIT, respectively. The numbers of subjects who required a colonoscopic examination to detect 1 advanced neoplasm were 18 in the colonoscopy group, 10 in the FIT group, and 11 in the risk-adapted screening group. DISCUSSION: For baseline screening, the risk-adapted screening approach showed a high participation rate, and its diagnostic yield was superior to that of FIT at a similarly low load of colonoscopy.